La révolution algérienne et la « guerre froide » (1954-1962) - Pervillé, Guy (Études internationales, 1985)
To the French military, still recovering from their defeat in Indochina, the Algerian war was but the final outcome of the "subversive war" carried out by international communism against the colonial empires of the "imperialistic" powers since 1920. The historical analysis does not corroborate this far too unlateral interpretation of the complex and ambiguous relations which existed between the communist and the nationalist movements of Algeria: the algerian FLN in the beginning was no less anticommunist than antinationalist. However, the strategic and diplomatic needs of its struggle against France led it to lean progressively towards the "socialist" States instead of the "imperialistic" West, thereby foregoing its initial neutralism. This has profoundly affected the paths taken by independent Algeria.